Post-vaccination leptospiral antibody titers among pet dogs in Malaysia - SH, Goh; KH, Khor; SF, Lau; S, Khairani-Bejo; AR, Sabri (Unique Scientific Publishers, 2022)
Vaccine immunity among Malaysian dogs with its diverse circulating serovars, is still debatable. The recommended vaccination protocol was implemented on a local level, but there was little local documentation of vaccine antibody titer production. This study evaluated the duration and magnitude of antibody titers before, during and after vaccination in both overtly healthy puppies and adult dogs. Puppies (n=20; 6-8 weeks) and adult dogs (n=20; 1-5 years old) were recruited. The dogs were vaccinated with a commercial quadrivalent vaccine (Icterohaemorrhagiae, Canicola, Grippotyphosa and Pomona) according to guidelines [World Small Animal Veterinary Association (WSAVA)]. Blood was sampled at pre- and post-vaccination up to one-year duration at intervals of 2, 4, 6, 8, 10, 12 weeks followed by 6, 9, 12 months. Serum was tested against the vaccine serovars using microscopic agglutination test (MAT) while whole blood for polymerase chain reaction (PCR). The antibody titer in puppies ranged between 1:50 to 1:200 was present for 6 months whereas the adults had higher titer of between 1:50 to 1:800 for a duration of one year. The antibody titers detected was the highest and persisted the longest for serovar Icterohaemorrhagiae followed by serovars Canicola, Grippotyphosa and Pomona. All dogs were PCR negative throughout the study period. Consideration should be taken when interpreting MAT results of clinical cases with presence of vaccine antibodies, requiring paired serum for better serodiagnosis. MAT remains a gold standard serological method for diagnosis and surveillance, current findings may become a basis of comparison allowing better interpretation and improved usability.